2003
DOI: 10.1046/j.1440-1843.2003.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the rheological properties of airway mucus on cough sound generation

Abstract: The rheological properties of the airway mucus influenced cough sound generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…In humans, it is not known how much mucus is required and where it has to be located for the human ear to detect presence of a moist cough. It is likely that mucus in the large airways is required for detectable difference in cough quality as the sound of cough is generated from vibration of larger airways and laryngeal structures during turbulent flow in expiration [16,17]. Laminar airflow, which occurs in smaller airways, is inaudible [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, it is not known how much mucus is required and where it has to be located for the human ear to detect presence of a moist cough. It is likely that mucus in the large airways is required for detectable difference in cough quality as the sound of cough is generated from vibration of larger airways and laryngeal structures during turbulent flow in expiration [16,17]. Laminar airflow, which occurs in smaller airways, is inaudible [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings support this and it is not surprising that when the cough is dry, BS grades were less. The rheological properties of airway mucus also influence cough sound [17]. It is not known how airway secretions in the more peripheral airways influences the sound of cough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not known as to how differences in vocal fold configuration influence the acoustics of cough in both sexes. Hashimoto et al (2003) demonstrated the effect of the rheological properties of airway mucus to cough sound production. Their study was based on examination of voluntary cough and sputum from patients with chronic productive cough.…”
Section: First Phasementioning
confidence: 99%
“…In humans, it is not known how much mucus is required and where it has to be located for the human ear to detect presence of a moist cough. It is likely that mucus in the large airways is required for detectable difference in cough quality, as the sound of cough is generated from vibration of larger airways and laryngeal structures during turbulent flow in expiration [47,49]. Laminar airflow, which occurs in smaller airways, is inaudible [50].…”
Section: Wet/moist or Productive Cough Vs Dry Coughmentioning
confidence: 99%